Autonomous Vehicles – Challenges for the Insurance Industry - Majewski, Piotr (Olsztyn Economic Journal, 2017)
The objective of this article is to identify and analyse opportunities and threats for the insurance industry related to the popularisation of autonomous vehicles. The analysis uses the data and forecasts included in reports of independent research institutions, which forecast the tempo of development of autonomous vehicle technologies. In the following few years, the global model of transport is going to change as it will gradually move away from the model of possessing individual vehicles and towards using a fleet of autonomous vehicles depending on current needs. The fundamental motivation for changes will be safety, comfort and lower costs. A direct result of the technological revolution for the insurance industry is a reduction of the amount of paid compensation, which is related to the improvement in the safety of road traffic. However, the new model of individual transport is going to dramatically reduce the number of vehicles on roads, and therefore it will result in a significant drop in the income for insurers coming from selling vehicle insurance policies, which currently is one of the most significant sources of income for numerous markets. (original abstract)